Оборонительные сооружения акрополя Булганакского городища - Храпунов, И.Н.; Мульд, С.А. (Материалы по археологии, истории и этнографии Таврии, 1993)
Булганакское позднескифское городище расположено в центральном Крыму, в 15 км к западу от Симферополя. Оно занимает вершину высокого холма, возвышающегося над долиной реки Западный Булганак. С напольной стороны поселение было защищено оборонительным валом, который не сохранился. Late Scythian Boulganak settlement is situated at a distance of 15 kms to the west from Simferopol. It occupies the top of the hill. From outside the settlement was protected by the defensive rampart which has not remained. The northern part of the hill, the so-called acropolis, was defended with one more line of defensive constructions. T’he area of the acropolis is more than 4,000 m", that is approximately 1/12 of the area of the whole settlement